Hemerodromia Meigen (Diptera, Empididae, Hemerodromiinae) from the state of Maranhão, Brazil: description of six new species and new records - Martins, Alana E.s.; Câmara, Josenir T.; Limeira-De-Oliveira, Francisco (Zootaxa, 2025)
After analyzing 191 specimens of Hemerodromia Meigen, six new species were identified: Hemerodromia bradleyi sp. nov., H. gurupi sp. nov., H. joanae sp. nov., H. joseaugustoi sp. nov., H. maranhensis sp. nov. and H. rafaeli sp. nov. In addition, new records for two species are presented: H. brevicercata Câmara, Takiya, Plant & Rafael and H. cercusdilatata Câmara, Plant & Rafael. The new species and the female of H. brevicercata are described and illustrated.